Logic, language, and computation 8th International Tbilisi Symposium on Logic, Language, and Computation, TbiLLC 2009, Bakuriani, Georgia, September 21-25, 2009. Revised Selected Papers - International Tbilisi Symposium on Logic, Language, and Computation 2009 Tbilisi, Georgia); Bezhanishvili, Nick.; Löbner, Sebastian; Schwabe, Kerstin; Spada, Luca.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Edited in collaboration with FoLLI, the Association of Logic, Language and Information, this book constitutes the refereed proceedings of the 8th International Tbilisi Symposium on Logic, Language, and Computation, TbiLLC 2009, held in Bakuriani, Georgia, in September 2009. The 20 revised full papers included in the book were carefully reviewed and selected from numerous presentations given at the symposium. The focus of the papers is on the following topics: natural language syntax, semantics, and pragmatics; constructive, modal and algebraic logic; linguistic typology and semantic universals; logics for artificial intelligence; information retrieval, query answer systems; logic, games, and formal pragmatics; language evolution and learnability; computational social choice; historical linguistics, history of logic.
Electronic reproduction.
Keywords: Computer logic -- Congresses; Programming languages (Electronic computers) -- Semantics -- Congresses; Computational linguistics -- Congresses; Electronic books